Poetic prose: A format in revival - Huárag Álvarez, Eduardo (2024)
This essay points out a revival of poetic prose in contemporary literature. It underlines that some poetic prose shares a poem’s main verbal features, while others assume what is typical of short stories: the exactly right word. It comments on some poetic prose by Charles Baudelaire and César Vallejo illustrating these ideas, intertwingled with some of Julio Cortázar’s stands on the notion of short story. Then, this essay focuses on Leo Almeida’s poetic prose, in which he uses his anti-system and irreverent point of view to innovatively highlight people’s marginality and ancestral cultures’ dispossession.